Community based management and sustainable livelihood of island fishers of Bangladesh - Md. Nurul Islam, Gazi; Raja Abdullah, Nik Mustapha (Penerbit Universiti Putra Malaysia, 2010)
This book investigates the impact of community based fisheries management (CBFM) project on household’s welfare in Bangladesh by investigating how the various types of assets contribute to household income. This book describes about the traditional fisheries management approach that exploited the poor fishers. Following this, the book highlights the important factor that contribute to household’s income of poor fisher by utilizing sustainable livehoods approach. This book concludes with policy recommendations for sustainable development of commmunity based approach in the island fisheries of Bangladesh to achieve development goals of poverty alleviation and human development in Bangladesh.